Ecophysiological study on the salt tolerance of a pannonian endemism (Lepidium crassifolium (W. et K.)) in inland saline area - Mile, Orsolya (Acta Biologica Szegediensis, 2002)
In the inland salin e are a two structurally different sands of Lepidio-Puccinellietum limosae community can be distinguised: open stand with low plant cover (mostly by Lepidium crassifolium) and closed stand with dense plant cover (mostly by Puccinellia limosa). The open habitat can be characterised by higher salinity degree. The leaf area of L. crassifolium is significantly lower on the open stand. The high water content per unit leaf area indicates the succulent character of the species and is involved in the avoidance of high salt (Na+) concentrations in the most saline habitat. There was remarkable accumulation of proline in leaves that can actas an osmotically active compound in the citoplasm. The osmotic potential of the tissue sap follows the changes of the proline concentrations, both diurnally and with the differences of habitats. Significant midday depression of Fv/Fm was found in the open habitat due to the unfavourable soil conditions and other additional abiotic factors such as higher irradiance and temperature.